2015
DOI: 10.1016/j.cmi.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Adult bacterial meningitis—a quality registry study: earlier treatment and favourable outcome if initial management by infectious diseases physicians

Abstract: Acute bacterial meningitis (ABM) is challenging for the admitting physician because it is a rare but fulminant disease, usually presenting without typical symptoms, and rapid treatment is pivotal. The purpose of this study was to evaluate the effect of initial management by infectious diseases (ID) physicians vs. non-ID physicians. A total of 520 consecutive adults (>17 years old), 110 with initial ID management and 410 with non-ID management, registered in the Swedish quality registry for community-acquired A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Although antimicrobials are critical for limiting CNS damage by proliferating pathogens, antimicrobial treatment without control of inflammation may result in paradoxically worse outcomes by stimulating the release of bacterial or fungal components that further provoke immunopathological responses adjacent to brain parenchyma 69,70 . Consistent with this, survivors of acute bacterial meningitis caused by Streptococcus pneumoniae or Neisseria meningitides may show persistent neurological deficits, including cognitive dysfunction or dementia, even if they received a timely diagnosis and treatment 71 . Monocyte-derived macrophages in the CNS, particularly meningeal and perivascular macrophages, have a protective role during bacterial meningitis 72 .…”
Section: Infections Of Csf Compartments and Brain Functionmentioning
confidence: 61%
“…Although antimicrobials are critical for limiting CNS damage by proliferating pathogens, antimicrobial treatment without control of inflammation may result in paradoxically worse outcomes by stimulating the release of bacterial or fungal components that further provoke immunopathological responses adjacent to brain parenchyma 69,70 . Consistent with this, survivors of acute bacterial meningitis caused by Streptococcus pneumoniae or Neisseria meningitides may show persistent neurological deficits, including cognitive dysfunction or dementia, even if they received a timely diagnosis and treatment 71 . Monocyte-derived macrophages in the CNS, particularly meningeal and perivascular macrophages, have a protective role during bacterial meningitis 72 .…”
Section: Infections Of Csf Compartments and Brain Functionmentioning
confidence: 61%
“…The study compared initial treatment performed by ID versus non-ID physicians. 24 The authors observed that appropriate treatment was achieved more frequently by ID physicians than by non-ID physicians with a trend for decreased mortality and sequelae at follow-up. Another retrospective study performed in Denmark evaluated the outcome of patients with late diagnosis of CABM.…”
Section: Meningitismentioning
confidence: 97%
“…In one study, patients with bacterial meningitis who were managed by infectious diseases physicians were significantly more likely to commence antibiotics within 1 h of presentation and to receive dexamethasone, and were less likely to experience treatment delays while awaiting neuroimaging. 5…”
Section: Managementmentioning
confidence: 99%
“…1 Despite ongoing advances in diagnostic methods and treatment strategies, mortality remains as high as 30% in pneumococcal meningitis and 5-10% in meningococcal meningitis. [4][5][6] It is critical that clinicians recognise the need to prioritise initial investigations while not delaying life-saving treatment with dexamethasone and antibiotics, which should be administered as soon as possible within the first hour following presumptive diagnosis. [4][5][6] It is critical that clinicians recognise the need to prioritise initial investigations while not delaying life-saving treatment with dexamethasone and antibiotics, which should be administered as soon as possible within the first hour following presumptive diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation